Extreme soil surface temperatures reflect need to rethink agronomic management. Issue 1 (19th February 2020) - O'Brien, Peter L.; Hatfield, Jerry L.
Abstract: The soil surface exists at the soil–atmosphere interface and is critical in regulating transfers of water, energy, and nutrients in agroecosystems. Soil surface temperature plays an important role in the rate and quantity at which these resources cross the interface, as temperature regulates numerous physical, chemical, and biological processes. Many current management practices manipulate soil surface temperatures, especially through tillage or residue management, to create conditions suitable for early‐season crop growth. However, these conditions persist beyond plant establishment and have the potential to develop extremely high temperatures, even in historically mild climates. We show the potential for extreme maximum soil surface temperatures in Iowa after crop establishment but before canopy closure and discuss possible consequences of those temperatures. Given the conditions required to develop extreme maximum temperatures, we contend that soil surface temperatures may be an indicator of conditions that are inconsistent with highly productive, sustainable, efficient agroecosystems.